Implementation of Ball Object Recognition Using Augmented Reality for Elementary School Level - Sari, Indah Purnama; Syafrayani, Putri Rizki; Andani, Salsabila Maisah (Jurnal Pendidikan, Kesehatan dan Olahraga, 2024)
Technology is developing rapidly in this modern era. This fast-developing technology helps humans deal with various kinds of problems. One of the developing technologies is augmented reality. Augmented reality can solve the problem for someone who wants to see their designs appear in the real world. Not only that, augmented reality can also be built on Android using the multimedia application development method and can be built using the Unity 3D engine. In Unity the objects used can be made using a 3D blender and the Vuforia Engine for Augmented Reality, the objects used are basketballs and baseballs.